Research and application of detection platform for distribution primary and secondary fusion switchgear. Issue 1 (1st December 2022) - Zhang, Xinyu; Nie, Yu; Zhao, Chuanzong; Du, Wei; Wang, Yanan; Cai, Zhiwei; Dong, Wenhai; Liu, Yanbing
Abstract: China's power enterprises are actively promoting the combinations of primary and secondary devices for distribution switchgear. However, these devices are still being tested separately, and the testing devices are bulky and occupy a large area. In this regard, we propose a new type of testing platform that can achieve three functions: testing for primary devices, testing for a system that integrates primary and secondary devices, and testing for distribution terminals. Hardware components, plug-in modules, and internal interfaces are designed in a standardized and compact manner, and genetic algorithms are used to automatically generate test samples. The integrated test platform for switch sets is miniaturized and portable, and its test environment is more in line with the field test, thus offering more efficient and reliable test results compared to traditional testing devices.